Maternal Exposure to Non-nutritive Sweeteners Impacts Progeny’s Metabolism and Microbiome - Olivier-Van Stichelen, Stephanie; Rother, Kristina I.; Hanover, John A. (Frontiers in Microbiology, 2019)
Non-nutritive sweeteners (NNS) are marketed as sugar alternatives providing sweet taste with few or no calories. Yet their consumption has been linked to metabolic dysfunction and changes in the gut microbiome. NNS exposure mostly originates from diet beverages and sweetener packages in adults or breastmilk in infants. Consequences of early life exposure remain largely unknown. We exposed pregnant and lactating mice to NNS (sucralose, acesulfame-K) at doses relevant for human consumption. While the pups’ exposure was low, metabolic changes were drastic, indicating extensive downregulation of hepatic detoxification mechanisms and changes in bacterial metabolites. Microbiome profiling confirmed a significant increase in firmicutes and a striking decrease of Akkermansia muciniphila. Similar microbiome alterations in humans have been linked to metabolic disease and obesity. While our findings need to be reproduced in humans, they suggest that NNS consumption during pregnancy and lactation may have adverse effects on infant metabolism.